Factors affecting VAT Receipts: Amount of PKP, Tax Incentives, Consumption and Inflation (Literature Review MKN) - Herty Safitry Yunintasari; Frenadi Irianto; Cris Kuntadi (Dinasti Publisher, 2023)
In a research or scientific work, previous research or related research is very important. Previous or relevant research helps strengthen the theories and phenomena that underlie the relationship or influence between variables. This article examines the aspects that influence the application of VAT, namely: the amount of PKP, tax and consumption incentives, a literature study on state financial management. The aim of this article is to provide hypotheses about factor influence for use in future studies. The findings from this literature review are as follows: Amount of PKP, Tax Incentives, Consumption and Inflation affect VAT Receipts.